Modulation of the skin microbiome in cutaneous T-cell lymphoma delays tumour growth and increases survival in the murine EL4 model - Dey, Saptaswa; Vieyra-Garcia, Pablo Augusto; Joshi, Aaroh Anand; Trajanoski, Slave; Wolf, Peter (Frontiers in Immunology, 2024)
Cutaneous T-cell lymphomas (CTCL) are a group of lymphoproliferative disorders of skin-homing T cells causing chronic inflammation. These disorders cause impairment of the immune environment, which leads to severe infections and/or sepsis due to dysbiosis. In this study, we elucidated the host-microbial interaction in CTCL that occurs during the phototherapeutic treatment regime and determined whether modulation of the skin microbiota could beneficially affect the course of CTCL. EL4 T-cell lymphoma cells were intradermally grafted on the back of C57BL/6 mice. Animals were treated with conventional therapeutics such as psoralen + UVA (PUVA) or UVB in the presence or absence of topical antibiotic treatment (neomycin, bacitracin, and polymyxin B sulfate) as an adjuvant. Microbial colonization of the skin was assessed to correlate with disease severity and tumor growth. Triple antibiotic treatment significantly delayed tumor occurrence (p = 0.026), which prolonged the survival of the mice (p=0.033). Allocation to phototherapeutic agents PUVA, UVB, or none of these, along with antibiotic intervention, reduced the tumor growth significantly (p=0.0327, p ≤ 0.0001, p ≤ 0.0001, respectively). The beta diversity indices calculated using the Bray−Curtis model showed that the microbial population significantly differed after antibiotic treatment (p=0.001). Upon modulating the skin microbiome by antibiotic treatment, we saw an increase in commensal Clostridium species, e.g., Lachnospiraceae sp. (p=0.0008), Ruminococcaceae sp. (p=0.0001)., Blautia sp. (p=0.007) and a significant reduction in facultative pathogens Corynebacterium sp. (p=0.0009), Pelomonas sp. (p=0.0306), Streptococcus sp. (p ≥ 0.0001), Pseudomonas sp. (p=0.0358), and Cutibacterium sp. (p=0.0237). Intriguingly, we observed a significant decrease in Staphylococcus aureus frequency (p=0.0001) but an increase in the overall detection frequency of the Staphylococcus genus, indicating that antibiotic treatment helped regain the microbial balance and increased the number of non-pathogenic Staphylococcus populations. These study findings show that modulating microbiota by topical antibiotic treatment helps to restore microbial balance by diminishing the numbers of pathogenic microbes, which, in turn, reduces chronic inflammation, delays tumor growth, and increases survival rates in our CTCL model. These findings support the rationale to modulate the microbial milieu during the disease course of CTCL and indicate its therapeutic potential.